2019
DOI: 10.12688/wellcomeopenres.15389.2
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Lipoarabinomannan Assay using Cerebrospinal fluid for the diagnosis of Tuberculous meningitis among HIV patients

Abstract: Background: The diagnostic utility of the Mycobacteria tuberculosis lipoarabinomannan (TB-LAM) antigen lateral flow assay on cerebrospinal fluid (CSF) for the diagnosis of tuberculous meningitis (TBM) has not been extensively studied and the few published studies have conflicting results. Methods: Lumbar CSF from 59 HIV-positive patients with suspected TBM was tested with TB-LAM and Xpert MTB/Rif Ultra. The diagnostic performance of CSF TB-LAM was compared to positive CSF Xpert MTB/Rif Ultra (definite TBM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The detection of M. tuberculosis DNA in CSF samples using nucleic acid amplification tests (NAATs) are a widely used diagnostic method (Marais et al, 2010). In recent years, some studies on NAATs (Modi et al, 2016Jyothy et al, 2019Kwizera et al, 2019;Pormohammad et al, 2019;Siddiqi et al, 2019;Poplin et al, 2020;Slane and Unakal, 2021) reported a potential to rule in or confirm diagnosis (specificity, 80%-100%), but low sensitivity (~40%-96%) precludes the use of these tests torule out TBM. Up to now, adenosine deaminase (ADA) is still a hot spot in TB diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of M. tuberculosis DNA in CSF samples using nucleic acid amplification tests (NAATs) are a widely used diagnostic method (Marais et al, 2010). In recent years, some studies on NAATs (Modi et al, 2016Jyothy et al, 2019Kwizera et al, 2019;Pormohammad et al, 2019;Siddiqi et al, 2019;Poplin et al, 2020;Slane and Unakal, 2021) reported a potential to rule in or confirm diagnosis (specificity, 80%-100%), but low sensitivity (~40%-96%) precludes the use of these tests torule out TBM. Up to now, adenosine deaminase (ADA) is still a hot spot in TB diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, efforts to utilize this assay on CSF for tuberculous meningitis have been suboptimal with poor sensitivity, although a positive CSF lipoarabinomannan antigen in people with HIV and tuberculous meningitis was correlated with higher mortality compared with patients with negative CSF lipoarabinomannan antigen. 20,24 Interferon gamma release assays are blood tests for detecting levels of interferon gamma released by T cells when exposed to TB antigens and are widely used to diagnose systemic TB. These assays include QuantiFERON (Qiagen), TB Gold (Qiagen), and T-Spot.TB (Oxford Immunotec).…”
Section: Diagnosismentioning
confidence: 99%
“…Lateral flow assays to detect mycobacteria lipoarabinomannan antigen, a polysaccharide chain found on mycobacterial cell walls, in the urine have been used as a point-of-care test to detect disseminated TB infection, especially in people with HIV with severe immunocompromise. However, efforts to utilize this assay on CSF for tuberculous meningitis have been suboptimal with poor sensitivity, although a positive CSF lipoarabinomannan antigen in people with HIV and tuberculous meningitis was correlated with higher mortality compared with patients with negative CSF lipoarabinomannan antigen 20,24 …”
Section: Tuberculous Meningitismentioning
confidence: 99%
“…The unique characteristic of the test is that its sensitivity increases as CD4 T-cell count falls, with a sensitivity of 56% in those with CD4 <100 cells/ml 60 . Yet, in CSF, despite some initial optimism related to an autopsy-based study in Uganda, the Alere TB-LAM has shown poor sensitivity on lumbar CSF in Uganda 91 , 92 , along with a larger Zambian study which examined culture positive TBM in Zambia (TB-LAM sensitivity 22% (23/105)) 91 , 93 . The Alere TB-LAM is also limited by is susceptibility to individual reader interpretation of the darkness of the test line compared to the reference card ( Figure 4 ).…”
Section: Tbm Diagnosticsmentioning
confidence: 99%